Cryptocurrency in the Modern Economic System: Analysis of Functions, Regulations, and Islamic Legal Perspectives - Zainal Abidin Matondang; ismail pulungan (Journal of Islamic Financial Technology, 2025)
The rapid advancement of digital technology in the era of the Fourth Industrial Revolution has significantly transformed global financial systems, including the emergence of cryptocurrency as a digital currency and asset powered by blockchain technology. Cryptocurrency introduces a decentralized, transparent, and efficient transaction system without reliance on a central authority. However, its existence raises substantial debate regarding its functions, legality, and compliance with Islamic economic principles. This study aims to analyze the concept of cryptocurrency, its functions and characteristics, regulatory frameworks in Indonesia, and Islamic legal perspectives on its use as both a medium of exchange and a digital commodity. This research employs a library research method with a descriptive-analytical approach, utilizing data sourced from books, academic journals, government regulations, and fatwas issued by the Indonesian Council of Ulama (MUI). The findings indicate that cryptocurrency can function as a medium of exchange and an investment asset, but its high price volatility positions it more as a speculative instrument. In Indonesia, cryptocurrency is not recognized as a legal means of payment but is permitted as a tradable commodity under the supervision of Bappebti. From an Islamic economic perspective, cryptocurrency is considered prohibited (haram) as a currency due to elements of gharar and dharar, but it may be traded as a commodity if it fulfills the principles of clear value, clear benefit, and legitimate ownership. This study concludes that the use of cryptocurrency requires strong regulatory control and careful consideration to align with economic stability and Sharia compliance.